The Role of Banking Credit and Innovation Technology in Deindustrialization in Indonesia - Budiasih, Budiasih; Eliezer, Wisly Ryan (Faculty of Economic and Business, 2025)
Research Originality: This study contributes to the literature by being the first to investigate the cause of deindustrialization from the production side, considering banking credit and innovation technology by Kaldor’s Second Law, specifically focusing on a regional level in Indonesia.Research Objectives: To investigate the impact of banking credit and innovation technology on deindustrialization on a regional level in Indonesia.Research Methods: This research uses using panel data model on 34 provinces from 2017-2022 and a Fixed Effect Model (FEM) with a Seemingly Unrelated Regression (SUR) method, incorporating other control variables was used. Share of bank credit to the manufacturing industry is used as a proxy for bank credit, while internet usage is used as a proxy for innovation technology.Empirical Results: The results showed that deindustrialization occurs in Indonesia even at the regional level. Banking credit and innovation technology are key factors driving the increase in GVA’s share of the manufacturing industry in Indonesia. Prioritizing the quality of workers and improving international trade could also effectively increase the GVA share of the manufacturing industry.Implications: This study offered valuable insights into designing and implementing capital policy strategies and equalizing internet access as an accelerator of innovation in the context of technology improvement to increase the manufacturing industry's GVA share.JEL Classification: O14, O11, R58How to Cite:Budiasih., & Eliezer, W. R. (2025). The Role of Banking Credit and Innovation Technology in Deindustrialization in Indonesia. Etikonomi, 24(1), 285 – 298. https://doi.org/10.15408/etk.v24i1.38755.